Exploring second-career teachers' career change motivation - Christensen, Angela Ann, author; Timpson, William, advisor; Richburg, Robert W., committee member; O'Donnell-Allen, Cindy, committee member (Colorado State University. Libraries, 2003)
The purpose of this phenomenological study was to describe and analyze motivations of second-career teachers who join the teaching profession by using a phenomenological design describing the essence of the participants' experience resulting in a description of themes. The main research question was: What are the motivational factors influencing the second-career teachers' decision to become a teacher? How did these factors contribute to the decision? A semi-structured interview format with open-ended questions was used in conformity with commonly accepted phenomenological data collection procedures. Nine second-career teachers were each interviewed for approximately one hour. All interviews were audio taped and transcribed verbatim. Then transcripts were sent to all participants in order to assure accuracy. Data analysis began with a careful and methodical reading of each transcript. First a biography of each participant was included in order to understand each participant's unique background. Then a within-case analysis was performed on the themes of motivation. Afterwards, a cross-case analysis was conducted in order to find themes of motivation that were common to all the participants. Seven themes of motivation emerged from the data. These were: 1) back of mind teaching desire; 2) dislike of previous occupation; 3) spousal support; 4) teacher, friend, family member encouragement; 5) inspired awakening; 6) impact on society; and 7) role of Professional Development School. Potentially significant findings from this study included the addition of three themes of motivation not previously mentioned in literature. These findings included the role of spousal support, the role of teacher/friend/family member encouragement, and the role of a Professional Development School. Recommendations were included for universities, school districts, potential second-career teachers, and further research.
Keywords: teacher education